2014
DOI: 10.1007/s11096-014-9933-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Care: the PCNE definition 2013

Abstract: It was possible to paraphrase definitions of PhC using a standardised syntax focusing on the provider, recipient, subject, outcomes, and activities included in PhC practice. During a one-day workshop, experts in PhC research agreed on a definition, intended to be applicable for the present time, representative for various work settings, and valid for countries inside and outside of Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 13 publications
1
131
0
3
Order By: Relevance
“…However, one did not explore what components of pharmaceutical care were being delivered in each of the responding countries, perhaps an aspect worth further exploring in future work. Additionally, the level of implementation in the country was not assessed, neither was the understanding of the term pharmaceutical care assessed, a term that may encompass many clinical fields 21 , and these are two important limitations. It is important to reflect on the validity of the reported level of service provision, as it is much higher than what has been reported elsewhere 15 .…”
Section: The Technical Staff Of Pharmacies Comprises Pharmacists In Amentioning
confidence: 99%
“…However, one did not explore what components of pharmaceutical care were being delivered in each of the responding countries, perhaps an aspect worth further exploring in future work. Additionally, the level of implementation in the country was not assessed, neither was the understanding of the term pharmaceutical care assessed, a term that may encompass many clinical fields 21 , and these are two important limitations. It is important to reflect on the validity of the reported level of service provision, as it is much higher than what has been reported elsewhere 15 .…”
Section: The Technical Staff Of Pharmacies Comprises Pharmacists In Amentioning
confidence: 99%
“…Since the PhC philosophy encompasses the practice of clinical pharmacy regardless of the definitions adopted [6], and the two concepts mainly differ for the setting of reference (community and hospital respectively), the European pragmatic understanding was that PhC is mainly the pharmacist's professional care provided in a community pharmacy to the individual patient [7]. In 2013 the Pharmaceutical Care European Network defined PhC as 'the pharmacist's contribution to the care of individuals in order to optimize medicines use and improve health outcomes' [8]. Although recommending a multidisciplinary approach in accordance with other healthcare professionals (starting with physicians and nurses), the pharmacist was explicitly defined as the PhC primary provider.…”
Section: Phc Definition and Activitiesmentioning
confidence: 99%
“…This disagreement with the term PC may be related to the following aspects: -According to Hepler [24], the concept of PC stimulates the pharmacists' imagination, causing the pharmacist to emphasize more some ideas than others and forgetting that medication therapy cannot be provided without the collaboration of the patient and other health professionals. Its evidence is that Van Mil and Fernandez-Llimos [25], Machuca et al [26], Blackburn et al [27], Alina Martínez [28], have debated the PC concept, and recently, Allemann et al [29] performed a review of the PC's definitions found in the literature, in order to construct one that includes all existing ones.…”
Section: Pcas Approachesmentioning
confidence: 99%